Stigma and Discrimination Towards Mental Illness: Translation and Validation of the Turkish Version of the Attribution Questionnaire-27 (AQ-27-T). - Akyurek, Gokcen; Efe, Aysegul; Kayihan, Hulya (Community Mental Health Journal, 2019)
The stigmatization towards mental illness has significant effects on the quality of life both for the people with a psychiatric disorder and their families. The aim of this study was to translate the Attribution Questionnaire-27(AQ-27) to the Turkish language, and to evaluate the reliability and validity of new Turkish version on a multi-centered selected adult sample. Cultural adaptation was implemented according to the internationally suggested method. The Turkish version of AQ-27 (AQ-27-T) was applied to a total of 424 participants (221 females) included to study. As a result; a good internal consistency was obtained with a Cronbach's alpha of 0.88 for the total scale and ranging between 0.86 and 0.89 for the items, and a statistically significant test–retest reliability was detected (r = 0.79; p < 0.05). Fit indices of the model supported the factor structure and paths. AQ-27-T was determined as a reliable and valid questionnaire assessing stigmatization toward mental illness in Turkish population.